Explicit vs. tacit collusion: The impact of communication in oligopoly experiments - Miguel A. Fonseca; Hans-Theo Normann (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
We explore the difference between explicit and tacit collusion by investigating the impact communication has in experimental markets. For Bertrand oligopolies with various numbers of firms, we compare pricing behavior with and without the possibility to communicate among firms. We find strong evidence that talking helps to obtain higher profits for any number of firms, however, the gain from communicating is nonmonotonic in the number of firms, with medium-sized industries having the largest additional profit from talking. We also find that industries continue to collude successfully after communication is disabled. Communication supports fims in coordinating on collusive pricing schemes, and it is also used for conflict mediation.
Keywords: C7; C9; L4; L41; 330; cartels; collusion; communication; experiments; repeated games